Inducting effects of ionic liquid crystal modified-PEDOT:PSS on the performance of bulk heterojunction polymer solar cells1. Issue 65 (16th July 2015) - Wang, Xiaofeng; Hu, Siwei; Li, Qiujuan; Li, Fan; Yao, Kao; Shi, Meiying
<x xml:space="preserve">Abstract</x> Photovoltaic performance was improved in P3HT/PCBM bulk-heterojunction solar cells induced by ionic liquid crystals modified PEDOT:PSS anode buffer layer.